The influence of different doses and ratios of mineral fertilizers on the yield of winter rye in the Urals - D. G. Shishkov; V. R. Olekhov; M. T. Vasbieva (Аграрная наука Евро-Северо-Востока, 2023)
Winter rye is an important crop of the Non-Chernozem belt of Russia, the productivity of which depends on the use of fertilizers. The paper presents data on the agronomic and economic efficiency of cultivating Falenskaya 4 winter rye under conditions of long-term use of mineral fertilizers. The studies were carried out in 2019-2021 in Perm Region on sod-podzolic heavy loamy soil in a long-term stationary experiment based on a reduced factorial design (6x6x6) with a wide range of doses and NPK ratios. The highest yield in 2019 was obtained in N30P120K120 variant (3.07 t/ha), the highest payback of mineral fertilizers by grain was noted in N90 and N30P30K30 variants (6.00 and 5.69 kg of grain). The highest yield and payback of grain in the conditions of 2021 and for two years of research in average was obtained in the variant N90: in 2021, 3.01 t/ha and 13.96 kg of grain, for 2 years average – 2.95 t/ha and 9.82 kg of grain. The efficiency of nitrogen fertilizers has been proved by a regression equation for two years average, phosphoric and potash fertilizers did not have a significant effect. The rise in the yield increase occurred up to a nitrogen dose of 90 kg/ha and amounted to 0.42 t/ha at N90. The highest payback by grain was noted among nitrogen treatments – by N30 (7.3 kg of grain), with each increase in doses by 30 kg/ha, this indicator decreased linearly by 1.3 kg. The highest profitability over the years of research was obtained in the variant without fertilizers– 60 %, over two years in average. The profitability of using N90 was higher compared with the control only in 2021 – 50 % versus 43 %. All the studied doses of nitrogen used separately provided positive profitability, but the most cost-effective was the use of N30 and N60 – profitability was 52 and 45 %, respectively.